Identification and Macrolide-Lincosamide-Streptogramin B Resistance Phenotypes and Biofilm Formation of CoagulaseNegative Staphylococci Strains Isolated from Bloodstream infections in Türkiye - Özdemir, Sinem; Aydoğan, Okan; Köksal Çakırlar, Fatma (Cerrahpaşa Medical Journal, 2025)
Objective: This study aimed to determine the species, biofilm formation ability, and macrolide-lincosamidestreptogramin B (MLSB) resistance phenotypes of coagulase-negative staphylococci (CoNS) isolated from blood cultures. Methods: Three hundred CoNS strains isolated from blood samples of patients with bacteremia hospitalized in intensive care units and other services in the hospital between 2020 and 2023 were retrospectively evaluated. Blood cultures were analyzed using the Bactec-9120 system. Strains were identified using MALDI-TOF MS (Bruker Daltonics, Germany). Antimicrobial susceptibilities were determined using the Kirby–Bauer disc diffusion method on Mueller–Hinton agar and evaluated according to EUCAST standards. Biofilm formation was assessed by the Congo Red Agar method. Results: Among isolates, Staphylococcus epidermidis was the most prevalent species (57.6%; P < .05). Methicillin-resistant CoNS isolates (MRCoNS) were determined to be more resistant to antibiotics than methicillin-susceptible CoNS isolates (MSCoNS) (P < .001). None of the isolates were resistant to vancomycin, teicoplanin, and linezolid. A total of 222 MRCoNS isolates were phenotypically categorized as the inducible MLSB, constitutive MLSB, and efflux type resistance were determined in 36%, 9%, and 36% and in 78 MSCoNS isolates 8%, 15%, and 38%, respectively. Methicillin-resistant CoNS exhibited significantly higher biofilm formation rates (77%) compared to methicillin-susceptible isolates (P < .001). Conclusion: The results showed that S. epidermidis is the most common CoNS species isolated in bloodstream infections. Multidrug resistance and increased biofilm formation ability, which come with increasing methicillin resistance, can lead to infections that are difficult to treat. It is important to routinely determine the resistance status of these bacteria for effective antibiotic therapy and prevention of nosocomial infections. Cite this article as: Özdemir S, Aydoğan O, Köksal Çakırlar F. Identification and macrolide-lincosamide-streptogramin B resistance phenotypes and biofilm formation of coagulase-negative staphylococci strains isolated from bloodstream infections in Türkiye. Cerrahpaşa Med J 2025; 49, 0047, doi: 10.5152/cjm.2025.24047.